Brønsted Acid Catalyzed Cyclization of Inert N-Substituted Pyrroles to Benzo[f]pyrrolo[1,2-a][1,4]diazepines - Gao, Zeng; Qian, Jinlong; Yang, Huameng; Zhang, Jinlong; Jiang, Gaoxi (Synlett, 2021)
Two approaches involving intramolecular and intermolecular cyclization, respectively, have been developed for the direct and practical construction of a series of important benzo[f]pyrrolo[1,2-a][1,4]azepines by using Brønsted acid catalysts. Upon catalysis by TsOH, the intramolecular dehydroxylation/ring closure of 3-hydroxy-2-[2-(1H-pyrrol-1-yl)benzyl]isoindolin-1-ones provided various racemic benzo[f]pyrrolo[1,2-a][1,4]azepines in high yields. Furthermore, enantioenriched benzo[f]pyrrolo[1,2-a][1,4]azepines were also obtained by chiral phosphoric acid catalyzed intermolecular addition of [2-(1H-pyrrol-1-yl)phenyl]methanamines to 2-formylbenzoates under mild conditions.
Keywords: Brønsted acid catalysis; cyclization; pyrroles; intermolecular addition; azepines; asymmetric catalysis